2004
DOI: 10.1007/s00432-004-0635-y
|View full text |Cite
|
Sign up to set email alerts
|

Myeloma cell contamination of peripheral blood stem-cell grafts can predict the outcome in multiple myeloma patients after high-dose chemotherapy and autologous stem-cell transplantation

Abstract: Patients with graft contamination of more than 4.5 x 10(5) plasma cells kg(-1) had a high risk of early disease progression after high-dose chemotherapy. In vivo tumor cell purging prior to mobilization chemotherapy might be one strategy to improve the time to progression of high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 18 publications
0
44
2
Order By: Relevance
“…Of the four MM cell lines that were tested for reovirus purging efficacy, one demonstrated complete purging, whereas the others showed a significant tumor reduction. As less tumor burden in an autograft could lead to an advantage in PFS, 8 reovirus purging may be considered as an option for many MM patients. In an era where a personalized approach to medicine is sought, one might even envision that MM represents a malignancy where BM aspirates could easily be withdrawn from patients and tested for reovirus sensitivity before initiating either a treatment regimen or purging strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the four MM cell lines that were tested for reovirus purging efficacy, one demonstrated complete purging, whereas the others showed a significant tumor reduction. As less tumor burden in an autograft could lead to an advantage in PFS, 8 reovirus purging may be considered as an option for many MM patients. In an era where a personalized approach to medicine is sought, one might even envision that MM represents a malignancy where BM aspirates could easily be withdrawn from patients and tested for reovirus sensitivity before initiating either a treatment regimen or purging strategy.…”
Section: Discussionmentioning
confidence: 99%
“…8 In addition, syngeneic twin transplantation has shown significantly lower relapse risk than autotransplantation for MM, again suggesting that graft contamination may impact outcome following ASCT. 9,10 Although CD34 þ cell selection has been used as a purging modality in the clinic, several studies have demonstrated that even after CD34 þ cell selection, MRD could still be detected in MM patient autografts.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Various methods have been used to reduce tumor cell contamination in the apheresis product for autologous transplantation, but these methods failed to improve disease-free or overall survival. 29,30 To date, there is no evidence of tumor cell mobilization in plerixafor-treated patients in phase 2 studies.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cell contamination does occur and there is no consensus on the acceptable and safe limit of tumor cells in the apheresis product. [4][5][6][7][8][9][10][11] There are various assays to quantify tumor cell contamination with sensitivities ranging from 1/100 cells using flow cytometry to 1/100 000 cells using PCR. 12 Although PCR testing is the superior method in terms of sensitivity, it is impractical for clinical practice as it is expensive, time consuming and requires patient-specific primers to be produced from myeloma cell samples.…”
Section: Introductionmentioning
confidence: 99%